2018
DOI: 10.1111/1475-6773.13011
|View full text |Cite
|
Sign up to set email alerts
|

External Determinants of Veterans’ Utilization ofVAHealth Care

Abstract: Changes in alternative insurance coverage and other external determinants may affect VA health care spending. Policy makers should consider these factors in allocating VA resources to meet local demand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Quantitative survivorship was overestimated compared with national registries with captured patient populations. As with all health systems in the United States, VHA patients with other insurance options 20 may receive revision surgery elsewhere. Quantitative comparisons with other registries are difficult because our calculated survivorship is based on isolated implant component revision rates, whereas the AOANJRR and other national registries commonly report on implant pairs and define failure as revision for any reason, which may or may not include removal of the implant of interest.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative survivorship was overestimated compared with national registries with captured patient populations. As with all health systems in the United States, VHA patients with other insurance options 20 may receive revision surgery elsewhere. Quantitative comparisons with other registries are difficult because our calculated survivorship is based on isolated implant component revision rates, whereas the AOANJRR and other national registries commonly report on implant pairs and define failure as revision for any reason, which may or may not include removal of the implant of interest.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Among working-age males, Hanchate and colleagues found that greater Medicaid generosity and higher proportion of employer-sponsored insurance are associated with lower utilization of VHA care. 16 We extend those findings to show that higher private health insurance coverage in the region is associated with lower risk of preventable hospitalization or death for VHA patients. A higher proportion of health insurance coverage among enrollees, including Medicare, Medicaid or private insurance, reduces demand for VHA care.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that veterans with higher household median income tend to have private insurance and are less likely to use VHA care 7,15. The HPI measures changes in housing prices since 1991, representing financial gains for homeowners but increased financial pressure for renters 16. Hanchate et al16 found an effect of the HPI consistent with a higher proportion of renters among veterans, namely that a higher HPI increased utilization of VHA care.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations